Influence of Corticosteroids on Interleukin‐1β‐Stimulated Equine Chondrocyte Gene Expression. Issue 3 (8th October 2015) - Caron, John P.; Gandy, Jeff C.; Schmidt, Michelle; Hauptman, Joseph G.; Sordillo, Lorraine M.
Abstract : Objective: To compare the effects of triamcinolone acetonide (TA) and methylprednisolone acetate (MPA) on expression of selected chondrocyte genes in recombinant equine interleukin‐1β (reIL‐1β) stimulated articular cartilage explants. Design: In vitro experiment. Animals: Horses (n = 6). Procedures: Articular cartilage explants from 2‐ to 3‐ year‐old horses were exposed to reIL‐1β in the presence and absence of TA and MPA at 10 −7 and 10 −6 M. Resting levels of mRNA of anabolic and catabolic genes of chondrocyte origin were quantified using qPCR after 6‐ and 12‐hour incubations. Genes of interest included aggrecan interglobular domain, aggrecan, and collagen II, matrix metalloproteinases 3 and 13 (MMP3, MMP 13), aggrecanase 1, tissue inhibitor of matrix metalloproteinases 1 and 2 (TIMP 1, TIMP 2), BCL 2, vascular endothelial growth factor, and cyclooxygenase 2 (COX 2). Results: IL‐1β significantly influenced the expression of most transcripts. MPA and TA inhibited the induction of MMP 13 at 6 and 12 hours; an effect that was significant at 6 hours with MPA at 10 −7 M and TA at 10 −6 M. Similarly, COX 2 was induced by reIL‐1β and MPA and TA significantly inhibited its upregulation. TIMP 2 expression was reduced by reIL‐1β, an effect that was significantly abrogated by MPA and TA. There were no significant differences observed between glucocorticoids for any gene studied. Conclusions: No differential effects of MPA or TA on chondrocytic gene expression were identified suggesting that any divergent influences of these glucocorticoids on chondrocyte metabolism are posttranslational.